Quantification of Vitamins, Minerals, and Amino Acids in Black Walnut (Juglans nigra) - Antora, Salma Akter; Ho, Khanh-Van; Lin, Chung-Ho; Thomas, Andrew L.; Lovell, Sarah T.; Krishnaswamy, Kiruba (Frontiers in Nutrition, 2022)
This paper aims to quantify the micronutrients in black walnut and address its human health benefits. The metabolic profiling of 11 black walnut cultivars was accomplished using ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight high-resolution mass spectrometer. Results revealed that the highest concentration of vitamin B9 was present in cultivar “Daniel” (avg. relative signal intensity 229.53 × 104 mAU). “Surprise” and “Daniel” cultivars had the highest amount of vitamin B5. However, vitamin A, D3, E, and K showed no significant difference among the cultivars. The vitamin content levels among the cultivars were compared by applying one way ANOVA method with (P < 0.05) significance level. Mineral analysis for the black walnut kernel, Persian walnut, and black walnut protein powder was done using Inductively Coupled Plasma Optical Emission spectroscopy. The experimental data for black walnut kernel is 0.04 mg/g for Fe and 0.03 mg/g for Zn, and for black walnut, protein powder is 0.07 mg/g for Fe and 0.07 mg/g for Zn. The amino acid analysis and comparison with black walnut kernel show that black walnut flour and protein powder have a higher amount of essential and non-essential amino acids. Therefore, researchers, food process engineers, and food product developers should consider the health benefits of black walnuts and explore the commercial potential of this native agroforestry crop.